2017
DOI: 10.4172/2576-1471.1000160
|View full text |Cite
|
Sign up to set email alerts
|

Induced Physical Distension of Rat Mammary Glands Accelerates the Onset of Apoptosis and Involution

Abstract: Objective: Weaning is a process that results in a reduction in milk secretion, an increase in mammary epithelial cell (MEC) apoptosis, and involution of the mammary gland. The local mechanisms initiating MEC apoptosis and involution are unclear, although the physical morphology of the MEC may influence cell-cell and cell-extracellular matrix communication and thus may alter function. This study examined the effect of physical distension of alveoli on the early molecular events that occur at the onset of involu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…In support of a role for mechanotransduction, mammary cell stretch in vitro was associated with the induction of apoptotic pathways (Quaglino et al, 2009). Furthermore, studies in vivo demonstrated that acute physical distension of rat mammary glands with sucrose solution accelerated the induction of apoptosis, upregulation of the apoptotic factor activated signal transducer and activator of transcription-3, and loss of the extracellular matrix factor β1-integrin and tight junction factor occludin (Phyn et al, 2007). Recently, the distribution and morphological changes in the mechanosensors primary cilia during lactation and involution implicate a role in initiating involution of the mammary gland (Millier et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…In support of a role for mechanotransduction, mammary cell stretch in vitro was associated with the induction of apoptotic pathways (Quaglino et al, 2009). Furthermore, studies in vivo demonstrated that acute physical distension of rat mammary glands with sucrose solution accelerated the induction of apoptosis, upregulation of the apoptotic factor activated signal transducer and activator of transcription-3, and loss of the extracellular matrix factor β1-integrin and tight junction factor occludin (Phyn et al, 2007). Recently, the distribution and morphological changes in the mechanosensors primary cilia during lactation and involution implicate a role in initiating involution of the mammary gland (Millier et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Physical distension of the mammary gland, which results in changes in cell shape (Richardson, ), may also play a role by activating mechanotransduction pathways, leading to a loss of TJ integrity and cell‐ECM survival signaling (Davis et al, ; Stelwagen, ). In support of mechanotransduction, mammary cell stretch in vitro induces apoptotic pathways (Quaglino et al, ) and in vivo accelerates the induction of apoptosis and loss of the ECM factor β1‐integrin and the TJ protein occludin (Phyn et al, ). Furthermore, primary cilia, key signalling organelles for sensing biochemical and biophysical extracellular stimuli, have been implicated in initiating involution of the mammary gland (Millier et al, ; Biet et al, ).…”
mentioning
confidence: 99%
“…In support, cell-cell communication (Cooper et al, 2004), cell-extracellular matrix communication (Singh et al, 2005), and the primary cilia of mechanosensors (Millier et al, 2013;Biet et al, 2016) were disrupted following milk engorgement at the onset of involution of the bovine mammary gland. Furthermore, acute physical distension of rat mammary glands with sucrose solution in vivo accelerated the onset of apoptosis of MEC, disruption of cell-cell and cell-extracellular matrix communication, and activation of STAT3 (Phyn et al, 2007). In bovine, this treatment suppressed milk secretion (Stelwagen et al, 1998) and milk protein gene expression (Biet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%